The Certification of Forest and Issues of Biodiversity and Environmental Conservation - Gupta, H. S. (Indian Forester, 2012)
"Certification of the forest" has always been visualized with the objective that it helps the forest maintain its ecological integrity. Thus in a certified forest every aspect related to sustainability are addressed by having sound management practices, ensuring its ecological integrity etc. which leads to biodiversity conservation, environmental conservation and ultimately sustainable forestry. This paper makes an attempt to assess the efficacy of forest certification as a tool for ensuring these concerns for conservation of biodiversity and environment, in particular.